Lemba, 1650-1930: A Drum of Affliction in Africa and the New World - Janzen, John M. (Garland Publishing, Inc., 1982)
A sophisticated historical ethnography of a ritual system centered on the Lemba “fetish,” showing how it organized social and commercial relations in the hinterland of the Loango coast in the era of the slave trade and how, after its destruction under colonial rule, it survived in Haiti. Dense ethnography.
free